A physical study of Libyan olive oil using a set of sensor - Maznouk, Noura; Abkatra, Sultana; Omar, Rabeea; Almaarati, Ghiath (Libyan Journal of Science &Technology, 2022)
In this research, a set of gas sensors (Tagushi Gas Sensors) which consist of three sensors [TGS2611- TGS2612-TGS2620] were used. This set was then exposed to the Libyan olive oil vapor to identify it and to derive the special physical parameters (R0-S-SRV- tr). We noticed that this set showed a very good response to olive oil vapor in a short time. The parameter FPS (Fingerprint Sensor) which is the most important physical parameter can be used to distinguish and/or investigate several kinds of vapors